Sex-Chromosome Recombination in Common Frogs Brings Water to the Fountain-of-Youth. (30th January 2018) - Rodrigues, Nicolas; Studer, Tania; Dufresnes, Christophe; Perrin, Nicolas
Abstract: According to the canonical model of sex-chromosome evolution, the degeneration of Y or W chromosomes (as observed in mammals and birds, respectively) results from an arrest of recombination in the heterogametic sex, driven by the fixation of sexually antagonistic mutations. However, sex chromosomes have remained homomorphic in many lineages of fishes, amphibians, and nonavian reptiles. According to the "fountain-of-youth" model, this homomorphy results from occasional events of sex reversal. If recombination arrest in males is controlled by maleness per se (and not by genotype), then Y chromosomes are expected to recombine in XY females, preventing their long-term degeneration. Here, we provide field support for the fountain-of-youth, by showing that sex-chromosome recombination in Rana temporaria only depends on phenotypic sex: naturally occurring XX males show the same restriction of recombination as XY males (average map length ∼2 cM), while XY females recombine as much as XX females (average map length ∼150 cM). Our results challenge several common assumptions regarding the evolution of sex chromosomes, including the role of sexually antagonistic genes as drivers of recombination arrest, and that of chromosomal inversions as underlying mechanisms.